Development of Student Worksheets Based on Project Based Learning on the Material 'Indonesia Kaya Budaya' for Class IV SDIT Tiara Islamic School Pekanbaru - Wahyuni, Yulia Septi; Suriadi, Hari; Deprizon; Miaz, Yalvema (UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to develop a Student Worksheet (LKPD) based on Project-Based Learning (PjBL) integrated with Islamic values on the theme “Indonesia Kaya Budaya” for fourth-grade students at SDIT Tiara Islamic School Pekanbaru. The research employed the 4D development model (Define, Design, Develop, Disseminate), which includes needs analysis, design, expert validation, and limited trials. Data were collected through observations, validation questionnaires, practicality questionnaires, and student reflections. Expert validation results indicated that the LKPD falls into the